Hubungan Kadar Delta Like Ligand 1 (DLL-1) Serum dan Cairan Serebrospinal (CSS) Terhadap Derajat Keparahan Meningitis Tuberkulosis - Abdul Razak; Syarif Indra; Restu Susanti; Yuliarni Syafrita; Reno Bestari; Gunawan Septa Dinata (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Tuberculous meningitis (TBM) is an infection caused by Mycobacterium tuberculosis (M.tb) affecting the meninges, characterized by high morbidity rates. The prognosis of TBM is partially determined by clinical severity, classified according to the British Medical Research Council (BMRC) scale. Delta Like Ligand 1 (DLL-1) is a transmembrane protein that plays a role in the formation of lipid cells, which are essential for the survival, virulence, and defense of M.tb against the host immune system. DLL-1 expression can be induced by the stimulation of M.tb cell walls in response to the human immune system. This study aims to analyze the correlation between DLL-1 levels in the serum and cerebrospinal fluid (CSF) with the clinical severity of TBM patients. A cross-sectional study was conducted involving 30 TBM patients treated at M. Djamil Central General Hospital, Padang, from October 2025 to January 2026. Serum and CSF DLL-1 levels were measured using the enzyme-linked immunosorbent assay (ELISA) method, while TBM severity was assessed based on the BMRC criteria. Data analysis was performed using SPSS version 26.0 with a significance level of p < 0.05. The results of the analysis showed no significant difference in serum DLL-1 levels (p = 0.129) or CSS DLL-1 levels in relation to the severity of TBM (p = 0.097).